Implementasi Data Mining Untuk Estimasi Produktivitas Kacang Hijau Dengan Menggunakan Algoritma Regresi Linier Di Kabupaten Grobogan - Kusumaningrum, Yulinda; Asmiatun, Siti; Putri, Astrid Novita (Jurusan Teknologi Informasi Universitas Semarang, 2021)
The Grobogan Regency Agriculture Service is an agency that operates in the agricultural sector. One of the crop commodities in Grobogan Regency is green beans. Judging from the results obtained each year, green bean production in Grobogan Regency is inconsistent. The rise and fall of green bean productivity is influenced by several factors. Factors such as area, production, number of farmers and productivity can be estimated to determine the production of green beans in Grobogan Regency. Therefore, using the Multiple Linear Regression algorithm is expected to help to obtain results on how much green bean production is in Grogoban Regency as a reference for farmers to increase their green bean harvest each year. Based on the calculation results, it was found that the estimated productivity of green beans in Grobogan Regency reached 760.8297302 Tons/Ha, whereas previously the land was 865 Hectares (Ha) Keywords: data mining, linear regression, estimation, productivity, green beans